Collaborative Research: Techniques for Conducting Collaborative Research From the Science of Team Science (SciTS). Issue 1 (February 2020) - Turner, John R.; Baker, Rose
The Problem: The field of human resource development (HRD) is a multidisciplinary field of research and practice requiring collaboration. Unfortunately, the literature on how to conduct collaborative research is incomplete within HRD and other disciplines. Any breakdown in the communication, exchange of ideas, agreed-upon methodologies, or shared credit for dissemination has the potential of preventing research from moving forward. Promotion and tenure policies also hamper collaborative efforts in that these policies often reward individual initiative as opposed to collaborative outcomes. These behavioral patterns provide constraints to the improvement and betterment of efforts to changing of the guard. The Solution: This article highlights new and improved methods for working in collaborative environments. During an academic's transition and professional development, these methods will help emerging scholars, new to collaborative research, when facing the team science revolution. The Stakeholders: Scholars and scholar-practitioners engaged in collaborative research. Emerging scholars who are beginning their journey into collaborative research. Graduate students preparing for a career in academia.